Decisions of the Supreme Court in Cases for Rehabilitation in the Years 1988–1991 (Archives of Criminology, 1993)
Analysed in the paper have been decisions of the Criminal and Military Departments of the Supreme Court in cases for rehabilitation of political offenders convicted in the years 1944–1988. The material under analysis consisted of 531 cases examined due to extraordinary appeal which concerned the total of 1.276 persons, and 9 cases  (of 33 persons) in which proceedings were reinstituted. On the whole,  rehabilitation proceedings concerned 1.309 persons.Among the decisions appealed against in both the above modes, those passed in the years 1944–1956 form the largest group (56.7%); the second largest are decisions passed after December 13, 1981. The prevalence of cases from before 1956 is caused, amng other things, by the extreme repressiveness of penal policy of that period when state terror was lavishly applied and the fundamental principles of legality commonly infringed. The persons involved in  rehabilitation proceedings before the Supreme Court are but a slight percentage of those convicted in the years 1944–1956. Also the penalties imposed in that period were  extremely severe.  Of the 702 persons now involved in rehabilitation proceedings (and formerly convicted in the years 1944–1956), as many as 86 were originally  sentenced to death; 9 were sentenced to life,  and 289 – to over 5 years impisonment.The most frequently quoted ground for extraordinary appeal was misapplication of substantial law (230 cases). It is also worth stressing that many a time, error as to the established facts also resulted in such misapplication of substantial law.Of the 540 rehabilitation proceedings, as few as two yielded negative results.The most frequent decision was acquittal or discontinuance of proceedings basing on Art. 11point 1 of the code of criminal procedure (i.e. for the reasons identical to those that lead to acquittal). Such decisions were passed with respect to over 90% of persons involved in rehabilitation preceedings. As many as 73 persons were rehalilitated posthumously (as the death penalty had been duly executed in their case).The most frequently quoted ground for acquittal in the mode of extraordinary appeal was absence of the statutory features of a prohibited act  (272 cases) and of the factual ground for indictment (151 cases). Additionally, defendants  had been convicted in 46 cases despite of the fact that their acts had not been punishable at the time of commission and, in 24 cases, despite of circumstances that excluded criminal responsibility. Therefore, as many as 493 cases ended with conviction despite of explicit grounds for acquittal (only the formal definition of an offence taken into account at that). In cases in which proceedings were reinstituted, the main ground for acquittal was non-punishability of the act at the time of its commission. Thus verifying the sued decisions that had actually infringed legal provisions, the Supreme Court acted mainly as defender of the law.In 52 cases, defendants were acquitted due to absence of social danger of the act. What should be stressed here is the crucial importance of such decisions where absence of social danger is quoted as the sole ground for acquittal. This  removes the collision between a concrete provision of penal law and the basic human, values, and affords possibilities for a proper assessment of an act from the viewpoint of such fundamental rights and values (and not political or other criteria dictated by a current situation). The unjustly convicted could therefore be fully rehabilitated but their actual contribution to the act for which they had originally been convicted was not belittled.A characteristic tendency of the Supreme Court’s decisions in cases for rehabilitation was a full approval for non-violent struggle against violence: for peaceful means of opposing totalitarianism.As has been confirmed by the present analysis, penal law was a peculiar instrument of the totalitarian rule; the trials of that period aimed at disposing of the real or imagined political opponents. Owing to the rehabilitating decisions, many of those formerly convicted could now receive full moral satisfaction; additionally, those decisions rehabilitate the judicial system to some extent and speak up for law based on the basic human values.Attached to the paper is an appendix which contains data on persons once convicted to capital punishment and life imprisonment and rehabilitated by the Supreme Court, as well as lists of the judges who imposed such extremely severe penalties and of persons who decided on the execution of death penalties.